2016
DOI: 10.1021/acsphotonics.6b00405
|View full text |Cite
|
Sign up to set email alerts
|

Fast Room-Temperature Detection of Terahertz Quantum Cascade Lasers with Graphene-Loaded Bow-Tie Plasmonic Antenna Arrays

Abstract: We present a fast room-temperature terahertz detector based on interdigitated bow-tie antennas contacting graphene. Highly efficient photodetection was achieved by using two metals with different work functions as the arms of a bow-tie antenna contacting graphene. Arrays of the bow-ties were fabricated in order to enhance the responsivity and coupling of the incoming light to the detector, realizing an efficient imaging system. The device has been characterized and tested with a terahertz quantum cascade laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 35 publications
1
57
1
Order By: Relevance
“…[70], the authors demonstrated more than 1-GHz modulation speed (even though significant degradation was observed already above 200 MHz) and 86% modulation depth. In this work, InAlN/AlN/GaN/AlN/GaN double-channel heterostructures supported a 2DEG channel [68] and as a detector [13]. Reprinted from Jessop et al [68], with the permission of AIP Publishing.…”
Section: Amplitude Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[70], the authors demonstrated more than 1-GHz modulation speed (even though significant degradation was observed already above 200 MHz) and 86% modulation depth. In this work, InAlN/AlN/GaN/AlN/GaN double-channel heterostructures supported a 2DEG channel [68] and as a detector [13]. Reprinted from Jessop et al [68], with the permission of AIP Publishing.…”
Section: Amplitude Modulatorsmentioning
confidence: 99%
“…The continuous development of more efficient, integrated, stable, and economic femtosecond (fs) laser sources has greatly improved the state of the art of time domain spectroscopic (TDS) systems. The research into THz detectors has benefited from significant progress in recent years, from GaAs Schottky barrier diodes [10] to the development of detectors based on novel materials, such as graphene [11][12][13][14][15]. The evolution of the basic building blocks for an efficient, integrated THz circuitry has not progressed at the same rapid rate, due to the poor electromagnetic response of naturally occurring materials in this range.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the antennas are finally connected to the source and drain pads, they not only provide the plasmonic resonance capable of concentrating the light in the gap region, but they also act as electrodes, thus efficiently collecting all the photocurrent contributions arising from the illuminated graphene areas. According to [13], the detection mechanism is attributed to photoconduction, which implies an overall conductivity change of the graphene between the electrodes [2]. In this regards, our approach differs profoundly from the previous detector design [13] which was rather described as a photodetector, being based on p-n junctions.…”
Section: Introductionmentioning
confidence: 95%
“…The detection of THz radiation without using broadband timedomain spectroscopic systems, remains particularly elusive and is traditionally based on intrinsically slow (<100 Hz) devices such as pyroelectric detectors, Golay cells or cryogenic operating detectors, such as Si-bolometers. Alternatively, graphene and other bi-dimensional nanomaterials have been demonstrated to be valid alternative materials in several reviews [1][2][3] and research articles [4][5][6][7][8][9][10][11][12][13], where detection has been achieved through several distinct mechanisms, such as the photovoltaic, We present a fast room temperature terahertz detector based on graphene loaded plasmonic antenna arrays. The antenna elements, which are arranged in series and are shorted by graphene, are contacting source and drain metallic pads, thus providing both the optical resonant element and the electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation